Effect of PEEP, Zero PEEP and Intraabdominal Pressure Levels on Cerebral Oxygenation in the Morbidly Obese Undergoing Sleeve Gastrectomy - YORULMAZ, İLKNUR SUİDİYE; DEMİRARAN, YAVUZ; SALİHOĞLU, Ziya; Umutoglu, Tarik; ÖZAYDIN, İSMET; Dogan, Sami (My University, 2017)
The study is designed to determine the effect of zero end expiratory pressure (ZEEP) and 5mmHg positive end expiratory pressure (5PEEP) on cerebral oxymeter (CO) levels in morbidly obese (MO) patients. Study was performed on 60 morbidly obese patients between 18-60 years old, American Society of Anesthesiology 2-3 status, scheduled to undergo laparoscopic sleeve gastrectomy under general anesthesia. The patients were divided into two groups: those ventilated with no PEEP (group ZEEP, n = 30) and those ventilated with 5 cmH(2)O PEEP levels (group 5PEEP, n = 28). rSO(2) values were measured. Data were recorded as basal, after the induction (A ind) of anesthesia, 5 min before insufflation (BI), 5 min after insufflation (AI), 15, 30, 45, and 60 min after induction, 5 min before desufflation, and 5 min after desufflation (AD). Invasive arterial pressures, CO values, peripheral oxygen saturation, end tidal carbondioxide, and intraabdominal pressure (IAP) were recorded in these time periods in all groups. Arterial blood samples were analyzed in terms of the 5BI, 5AI, and 5AD periods. There was a negative correlation between IAP and left CO on pneumoperitoneum time in group 5PEEP. Correlation was observed between bilateral CO values and ideal body weight (IBW), lean body weight (LBW), body surface area BSA, in group ZEEP. Correlation was observed between IBW, LBW, and right CO values in group 5PEEP. PEEP application may have a protective effect on cerebral oxygenation.